(3eZGfj GdebGeGJ aj eYGfj GdebGeGJs - (3JGL GdOjf eMeO Hf YHO GdQMef Hf eMeO GdeSYhOj GdNQGSGfjs; (3GdMQjQj,J (B516 (3g` s ((3CMeO Hf eMeO GdLOhQj s)
(3ChdgG (B:s
(3hHYO, aEf EaJQGS ChGHO GdYQHjI, hGbJHGS GdaDGFO GdCOHjI TjeI dPhj GdCNWGQ eCdhag s
(3BNQgG (B:s
(3hGddg SHMGfg hJYGdi hdj GdeDefjf Cj jJhdi KhGHge heLGRGJge HMSf CYeGdge aj GdOfjG hGdBNQI gPG efJgi oLgO Gdoebd s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHI HgGeTgG JYdjbGJ hfbhd PGJ aGFOI hcJH fU GdebGeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs